Cryptocurrency Market Dynamics: Analyzing Trends And Patterns In Bitcoin - Hugo Prasetyo Winotoatmojo; Antonius Ary Setyawan; Akbar Ramadhan Hendraningrat; Jovita Grace Setiawati (Dinasti International Journal of Education Management And Social Science, 2024)
Consumer demand for speed, comfort, and security in financial transactions is rising along with the globalization of the business. As a result, we require a payment method that is dependable and simple for bank clients. A payment system is a set of arrangements that facilitates the exchange of value between individuals and financial institutions on a national and international level in order to deliver payments. A literature review, or literature review, is the research design used here. A literature review is an explanation of the hypotheses, conclusions, and other research materials that are gleaned from reference works and used as the foundation for further study. The literature review includes summaries, reviews, and the author's observations about a variety of literature sources (books, papers, slides, online material, and so forth) that address the subject under discussion. As it stands, Bitcoin is still the most popular cryptocurrency in terms of user base, market value, and popularity. Though certain altcoins are supported due to their better or more sophisticated features than Bitcoin, virtual currencies like Ethereum and Ripple, which are more commonly utilized as other enterprise solutions, are currently growing in popularity. Based on the current trajectory, cryptocurrencies are here to stay, but as time goes on, only a select handful will stand out as leaders in the face of growing competition and more visibility. The world of cryptocurrency may prove to be quite promising in the future as long as the bitcoin options market continues to gain traction, even with all the drawbacks that accompany it.